2009
DOI: 10.1007/s00415-009-5012-y
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone 10 days on/10 days off in patients with Duchenne muscular dystrophy

Abstract: Corticosteroids are effective in improving motor function in Duchenne muscular dystrophy (DMD) patients within 6 months-2 years of treatment initiation, but there is as yet no consensus on which treatment scheme is the best. We retrospectively analyzed data of 35 DMD patients who were treated with prednisone 0.75 mg/kg per day intermittently 10 days on/10 days off. Prednisone was started during the ambulant phase at age 3.5-9.7 years (median 6.5 years). The median period of treatment was 27 months (range 3-123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Bone strength, or mechanical properties, are compromised in these patients as evident by the occurrence of fragility fractures upon falling from standing or sitting height [4], [5], [6], [7]. Compromised bone strength in DMD is multi-factorial, likely including effects of failure to accumulate peak bone strength during growth as well as declines in bone health secondary to the muscle disease.…”
Section: Introductionmentioning
confidence: 99%
“…Bone strength, or mechanical properties, are compromised in these patients as evident by the occurrence of fragility fractures upon falling from standing or sitting height [4], [5], [6], [7]. Compromised bone strength in DMD is multi-factorial, likely including effects of failure to accumulate peak bone strength during growth as well as declines in bone health secondary to the muscle disease.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle weakness is a main clinical symptom and the target of treatment in DMD patients. Many treatment regimens have been reported previously, including daily [21] or intermittent dose regimens (on alternate days or 10 days on/10 days off [15]), with daily administration having a more favorable profile [22]. The most commonly used prednisone dosage was 0.75 mg/kg/day; a higher dose of 1.5 mg/kg/day was no more effective [23] and a lower dose of 0.3 mg/kg/day was less beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a randomized, blinded, clinical trial showed that 10 mg/kg prednisone administered only on weekends is as safe and effective over a 12-month treatment period as daily administration of 0.5 mg/kg prednisone in 4-year-old to 10-year-old boys with DMD [14]. Some studies have suggested that intermittent corticosteroid therapy over a 2-year period improves ambulatory function and causes relatively few adverse effects [15,16]. Even among patients who have lost ambulation ability, continued treatment is helpful in reducing the risk of progressive scoliosis and stabilizing pulmonary function [17,18].…”
Section: Introductionmentioning
confidence: 96%
“…The effect of an alternate, 10 days on/10 days off, 0.75 mg/kg prednisone regime has been investigated in a group of 35 DMD patients [14]. The treatment was initiated during the ambulant phase and the median period of treatment was 27 months.…”
Section: Steroid Treatment In Duchenne Muscular Dystrophymentioning
confidence: 99%